The effect of allopurinol on renal outcomes in patients with diabetic kidney disease: A systematic review and meta-analysis - Binbin Wu; Lili Chen; Yuankai Xu; Qingqing Duan; Zhibo Zheng; Zhigui Zheng; Dongyuan He (Kidney & Blood Pressure Research, 2022)
Background: Hyperuricemia is an independent risk factor for diabetic kidney disease (DKD) progression. Previous animal and cohort studies have reported that allopurinol administration could be of therapeutic benefit in diabetic subjects. However, there has been controversy regarding the effects of allopurinol on DKD. Objectives: The aim of our study is to investigate the efficacy of allopurinol on renal function in patients with DKD by meta-analysis of randomized controlled trials. Method: PubMed, EMBASE, and the Cochrane Library were searched from inception to October 2020. The primary outcome was a change in glomerular filtration rate (GFR). The secondary outcome was the change in albuminuria and serum UA. Two reviewers independently assessed for risk of bias and extracted data. Standardized mean difference (SMD) or weighted mean difference (WMD) was calculated with random effects models and was reported with corresponding 95% confidence intervals (CI). Grading of Recommendations Assessment, Development and Evaluation (GRADE) of the evidence was performed after meta-analysis. International prospective register of systematic reviews registration CRD42020219132. Results: From 642 potentially relevant citations, 3 studies were ultimately included. Our results showed evident reduction in serum UA after allopurinol intervention (WMD = -103.80, 95% CI -159.05, -48.55, I2= 76%; P = 0.04), with a high GRADE of evidence. However, allopurinol did not significantly improve GFR (WMD = 1.07, 95% CI -1.68, 3.82, I2= 33%; P = 0.45), with a moderate GRADE of evidence. There was no significant difference on improvement of albuminuria in patients of allopurinol and those in placebo groups (SMD = -0.26, 95% CI -1.03, 0.52, I2= 94%; P = 0.52), with a moderate GRADE of evidence. Conclusions: The present research showed that allopurinol did not significantly improve renal function and albuminuria in patients with DKD.